Exploring mobile learning development lifecycle with cultural context - Wan Abdul Rahim Wan Mohd Isa; Ahmad Iqbal Hakim Suhaimi; Nurulhuda Noordin; Rabiatul Adawiyah Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Based on the preliminary study, there are two problems that the development team faces; lack of development model or guideline with culture context for mobile learning developments and lack of cultural context in user interface and user experience of mobile learning development and practices. The main objectives are; (i) to propose Mobile Learning Development Lifecycle Cultural Model and to (ii) assess the proposed Mobile Learning Development Lifecycle Cultural Model. An IT scholar and five IT staff involved in mobile learning development based on the public and private sector at Klang Valley, Malaysia had been chosen for the interview session. The collected data has been analyzed by applying the thematic analysis approach. The first objective was achieved based on IT scholar reviewed on the model proposed. The IT scholar reviewed, (i) challenges on mobile learning development, (ii) theory of Hofstede on the design phase, (iii) user persona on the requirements phase, (iv) advantages of using the proposed model and (v) challenges on Mobile Learning Development Lifecycle Cultural Model. Then, the second objective was achieved by analyzing the qualitative information from the IT staff on the model proposed. The assessment was done by the IT staff for the Mobile Learning Development Lifecycle Cultural Model. There were four primary categories highlighted by the IT staffs which were (i) challenges on mobile learning development, (ii) overcome the challenges, (iii) important elements in mobile learning development and (iv) advantages of Mobile Learning Development Lifecycle Cultural Model. For future work, this study can include more IT scholar and IT staff from diverse positions from multiple organizations.